The case study handbook a student's guide - Ellet, William (Boston, Massachusetts Harvard Business Review Press, 2018)
If you're enrolled in an executive education or MBA program, you've probably encountered a powerful learning tool: the business case. But if you're like many people, you may find interpreting and writing about cases mystifying, challenging, or downright frustrating.That's not surprising: cases are not expository writing and good ones are often nonlinear and even misleading in their presentation and organization. Apply the conventional approach to understanding business cases, and you may waste time (at best) and arrive at faulty understandings (at worst). In The Case Study Handbook, William Ellet presents a potent new approach for analyzing, discussing, and writing about cases. Early chapters show how to classify cases according to the analytical task they require (solving a problem, making a decision, or forming an evaluation) and quickly establish a base of knowledge about a case. Strategies and templates, in addition to several sample Harvard Business School cases, help you apply the author's framework.Later in the book, Ellet shows how to write persuasive case-analytical essays based on the process laid out earlier. Extensive examples of effective and ineffective writing further reinforce your learning. The book also includes a chapter on how to talk about cases more effectively in class. The Case Study Handbook will be an indispensable learning aid for any current or prospective MBA or executive education student.--
What is the case method? : what's in it for you? -- Part I. Analyzing cases: What is a case? -- The skills you need to read and analyze a case -- How to analyze decision scenario cases -- How to analyze evaluation scenario cases -- How to analyze problem-diagnosis scenario cases -- Part II. Discussing cases: How to prepare and discuss cases -- Part III. Writing about cases: How to write case-based essays -- How to write decision scenario essays -- How to write evaluation scenario essays -- How to write problem-diagnosis scenario essays -- Part IV. Cases for analysis and writing: General Motors: Packard Electric Division -- Malaysia in the 1990s (A) -- Allentown Materials Corporation: the Electronic Products Division (abridged) -- Part V. Study guides for case analysis and writing: Study guide for decision scenario cases -- Study guide for evaluation scenario cases -- Study guide for problem-diagnosis scenario cases.
Includes index
Keywords: Management -- Case studies -- Study and teaching